Writing Without a Who: Reclaiming Authorship in the Age of Generative AI - ZAINUDIN, NUR AIMAN; JOHARI, ZAIDATUL HUSNA (Southeast Asian Journal on Open and Distance Learning, 2025)
The rise of generative artificial intelligence (AI) tools such as ChatGPT presents an ontological and ethical disruption to writing in education. As machines increasingly produce human-like texts, the meaning of authorship, originality, and the learner’s presence in their own writing comes into question. This concept paper explores the implications of AI-mediated writing through the dual philosophical lenses of Martin Heidegger and Hannah Arendt. Heidegger’s concept of enframing reveals how AI transforms writing into an efficient, optimized output, severing it from its poietic and disclosive potential. Arendt’s theory of action elaborates the risk of writing devolving into mere labor, stripping students of the opportunity to appear, speak, and act meaningfully in the world. A rehumanised pedagogy is proposed—one that reclaims writing as an act of becoming, relational presence, and political appearance. In this framework, AI is repositioned not as a surrogate author, but as a reflective tool within the learner’s dialogic and developmental space.